Plasma-assisted synthesis of MoS2. (4th October 2017) - Campbell, Philip M; Perini, Christopher J; Chiu, Johannes; Gupta, Atul; Ray, Hunter S; Chen, Hang; Wenzel, Kevin; Snyder, Eric; Wagner, Brent K; Ready, Jud; Vogel, Eric M
Abstract: There has been significant interest in transition metal dichalcogenides (TMDs), including MoS2, in recent years due to their potential application in novel electronic and optical devices. While synthesis methods have been developed for large-area films of MoS2, many of these techniques require synthesis temperatures of 800 °C or higher. As a result of the thermal budget, direct synthesis requiring high temperatures is incompatible with many integrated circuit processes as well as flexible substrates. This work explores several methods of plasma-assisted synthesis of MoS2 as a way to lower the synthesis temperature. The first approach used is conversion of a naturally oxidized molybdenum thin film to MoS2 using H2 S plasma. Conversion is demonstrated at temperatures as low as 400 °C, and the conversion is enabled by hydrogen radicals which reduce the oxidized molybdenum films. The second method is a vapor phase reaction incorporating thermally evaporated MoO3 exposed to a direct H2 S plasma, similar to chemical vapor deposition (CVD) synthesis of MoS2 . Synthesis at 400 °C results in formation of super-stoichiometric MoS2 in a beam-interrupted growth process. A final growth method relies on a cyclical process in which a small amount of Mo is sputtered onto the substrate and is subsequently sulfurized in a H2 S plasma. Similar results could be realized using an atomic layer deposition (ALD) process to deposit the Mo film. Compared to high temperature synthesis methods, the lower temperature samples are lower quality, potentially due to poor crystallinity or higher defect density in the films. Temperature-dependent conductivity measurements are consistent with hopping conduction in the plasma-assisted synthetic MoS2, suggesting a high degree of disorder in the low-temperature films. Optimization of the plasma-assisted synthesis process for slower growth rate and better stoichiometry is expected to lead to high quality films at low growth temperature.